STUDENTS PERCEPTION ON ETHNIC RELATIONS COURSES: A Case Study at Universiti Utara Malaysia - Muhammad Amar Mahmad (JICSA : Journal of Islamic Civilization in Southeast Asian, 2018)
The Ethnic Relations Course introduced in 2006 at Higher Education Institutions (IPT) is an attempt to address the issues of ethnic relations that are often an issue in country development. The course is a national medium towards creating an ethnical integration with diverse backgrounds of belief and culture. However, ethnic differences will certainly create diverse perceptions among students. If this is the case, then the offer of the course will not achieve its goal. The main objective of this study is to examine the students' attitudes based on the ethnic factors influencing the course offering. The research instrument was developed by the researcher based on the objectives of the course. Respondents were randomly selected from 300 people comprising of second semester Ethnic Relations course students in 2016/2017 at UUM. The findings showed that ethnic factors also influenced the perceptions difference between students towards the offer of Ethnic Relations course although not significant. To overcome this distinction, the government should extend the basic concepts of the course to students since the schooling.